Perchè prima l'Italia? Aspetti medici, geografici e pianificatori del Covid-19 (GEOmedia, 2020)
Why was Italy hit first among western countries? The organized research brought together the attention of doctors, geographers and planners to try to understand the origins of Covid-19 in Italy. Analyzing various data at the provincial level, we tried to include how environmental, geographical, socio-economic variables played a role in the 2020 pandemic in Italy.